“LRRK2: Autophagy and Lysosomal Activity” - Madureira, Marta; Connor-Robson, Natalie; Wade-Martins, Richard (Frontiers in Neuroscience, 2020)
It has been 15 years since the Leucine-rich repeat kinase 2 (LRRK2) gene was identified as the most common genetic cause for Parkinson’s disease (PD). The two most common mutations are the LRRK2-G2019S, located in the kinase domain, and the LRRK2-R1441C, located in the ROC-COR domain. While the LRRK2-G2019S mutation is associated with increased kinase activity, the LRRK2-R1441C exhibits a decreased GTPase activity and altered kinase activity. Multiple lines of evidence have linked the LRRK2 protein with a role in the autophagy pathway and with lysosomal activity in neurons. Neurons rely heavily on autophagy to recycle proteins and process cellular waste due to their post-mitotic state. Additionally, lysosomal activity decreases with age which can potentiate the accumulation of α-synuclein, the pathological hallmark of PD, and subsequently lead to the build-up of Lewy bodies observed in this disorder. This review provides an up to date summary of the LRRK2 field to understand its physiological role in the autophagy pathway in neurons and related cells. Careful assessment of how LRRK2 participates in the regulation of phagophore and autophagosome formation, autophagosome and lysosome fusion, lysosomal maturation, maintenance of lysosomal pH and calcium levels, and lysosomal protein degradation will be addressed. The autophagy pathway is a complex cellular process and due to the variety of LRRK2 models studied in the field, associated phenotypes have been reported to be seemingly conflicting. This review provides an in-depth discussion of different models to assess the normal and disease-associated role of the LRRK2 protein on autophagic function. Given the importance of the autophagy pathway in Parkinson’s pathogenesis it is particularly relevant to focus on the role of LRRK2 to discover novel therapeutic approaches that restore lysosomal protein degradation homeostasis.